Nanocarriers for pulmonary administration of peptides and therapeutic proteins. (January 2011) - Andrade, Fernanda; Videira, Mafalda; Ferreira, Domingos; Sarmento, Bruno
Peptides and therapeutic proteins have been the target of intense research and development in recent years by the pharmaceutical and biotechnology industry. Preferably, they are administered through the parenteral route, which is associated with reduced patient compliance. Formulations for noninvasive administration of peptides and therapeutic proteins are currently being developed. Among them, inhalation appears as a promising alternative for the administration of such products. Several formulations for pulmonary delivery are in various stages of development. Despite positive results, conventional formulations have some limitations such as reduced bioavailability and side effects. Nanocarriers may be an alternative way to overcome the problems of conventional formulations. Some nanocarrier-based formulations of peptides and therapeutic proteins are currently under development. The results obtained are promising, revealing the usefulness of these systems in the delivery of such drugs.